2018
DOI: 10.1111/jir.12494
|View full text |Cite
|
Sign up to set email alerts
|

An examination of perceptions of individuals with an intellectual disability, with and without co‐morbid schizophrenia: effects of labels on stigma

Abstract: Labels resulted in positive outcomes, particularly, when ID was co-morbid with schizophrenia. Schizophrenia stigma appears to be impacted by an ID label, indicating educating the public about the spectrum of co-morbidity may be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
1
2
0
1
Order By: Relevance
“…Notwithstanding concerns voiced about the negative effects of labelling, providing lay people with an ID label in the current study was associated with reduced stugma. Similar to a a recent study of people with ID with/without comorbid schizophrenia, those informed of the diagnostic label were more positive towards social contact than those who provided their own, potentially more stigmatising explanations for the person's behaviour [5]. Labelling was also associated with increased endorsement of biomedical causes and reduced endorsement of environmental causes.…”
Section: Plos Onesupporting
confidence: 69%
See 1 more Smart Citation
“…Notwithstanding concerns voiced about the negative effects of labelling, providing lay people with an ID label in the current study was associated with reduced stugma. Similar to a a recent study of people with ID with/without comorbid schizophrenia, those informed of the diagnostic label were more positive towards social contact than those who provided their own, potentially more stigmatising explanations for the person's behaviour [5]. Labelling was also associated with increased endorsement of biomedical causes and reduced endorsement of environmental causes.…”
Section: Plos Onesupporting
confidence: 69%
“…This has a direct negative effect on their quality of life and possibility for participation, contradicting the Convention on the Rights of Persons with Disabilities by the United Nations (UN-CRPD) [4]. Stigma towards people with ID is considered to be understudied [5], thus, to tackle prejudice and stigma, it's important to learn more about the nature of stigma and its presentations towards people with ID.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, schizophrenia was chosen because of its tendency to elicit polarizing reactions regarding the manifestation and lived experiences of the disorder. Specifically, research has found that the diagnosis of schizophrenia tends to evoke higher levels of stigma and a greater desire for social distancing among the general population than other types of mental illness (Jorm & Oh, 2009; Rasdale et al, 2018; Thompson et al, 2002; Webb et al, 2009). In addition, people with schizophrenia are generally seen as more dangerous, unpredictable, and capable of violence than individuals with other diagnoses (Jorm et al, 2012).…”
Section: Language Labels and Mental Illnessmentioning
confidence: 99%
“…Pandangan ini telah terinternalisasi pada sikap masyarakat terhadap penderita skizofrenia. Pandangan ini membentuk stigma dan terbangun pemahaman sosial bahwa pasien skizofrenia harus dikucilkan (Rasdale, Warman, & Phalen, 2018).…”
Section: Tema 1 : Pengajuan Pelatihanunclassified